Bacteriology and Antibiotic Sensitivity Pattern of Sputum in Patients with Acute Exacerbation of Chronic Obstructive Pulmonary Disease - Majumder, Md Mahabubul Islam; Shaha , Pinki; Ahmed , Mostaque; Uddin, Mohammad Nazim; Rahman , Mahabubur; Ahmed , Tarek (Medicine Today, 2022)
Introduction: Chronic obstructive pulmonary disease (COPD) is a major cause of chronic morbidity and mortality worldwide. Nowadays investigators need culture studies for proper selection of antibiotic, but it is a time consuming process. The choice of the antibiotic should be constituted on the bacterial sensitivity and resistance pattern. Objective: To identify the causative bacteriology and antibiotic sensitivity of sputum of chronic obstructive pulmonary disease patients with acute exacerbation. Materials and Methods: It was a prospective study in department of medicine Cumilla Medical College Hospital during the period of July 2019-2020. All the patients included in this study were above 37 years of age, diagnosed as acute exacerbation of COPD (AECOPD) were included in this study. Those patients were on antibiotic was advised to stop antibiotic for 48 hours and were included in this study. Fresh spot specimen as well as overnight collection of sputum samples were collected from each 257 patients of different age and sex groups in a sterile screw capped universal container. The specimen was labeled and transported to the microbiology laboratory for processing and cultured within half an hour of collection. Antibiotic susceptibility pattern was done following Kirby-Bauer disc diffusion method of clinical laboratory science (CLS) program. Results: Majority (45.5%) of the patients had growth of Klebsiella pneumoniae. All the isolated organisms except Acintobactor are mostly sensitive to Meropenum, Imipanum and Amikacin. In vitro sensitivity pattern against these antibiotics was more than 85%. Conclusion: Male is predominating and majority of them are older age group. Klebsiella pneumoniae, Pseudomonas and E. coli are common isolated organisms. Medicine Today 2022 Vol.34(1): 12-16